Ireland : First and Second Reviews Under the Extended Arrangement and Request for Rephasing of the Arrangement; Staff Report; Letter of Intent; Memorandum of Economic and Financial Policies; Technical Memorandum of Understanding; Letter of Intent and Memorandum of Understanding on Specific Economic Policy Conditionality (College of Commissioners); Staff Supplement; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2011)
Ireland has made progress in overcoming the economic crisis. The new coalition government's strategy for restoring sustained growth, sound public finances, and job creation has been put forward in the context of the European Union/IMF-supported program. On this basis, the government adopted a comprehensive strategy to reorganize and deleverage domestic banks, and to strengthen their capital base. Steadfast implementation of policies coupled with support from a comprehensive European plan will foster Ireland's economy.